Experimental Study of Exhaust Manifold Modification Using a Divided Tec on a Four-Stroke Motorcycle: Studi Eksperimental Modifikasi Exhaust Manifold Menggunakan Tec Bersekat pada Sepeda Motor Empat Langkah - Putro, Sartono; Adianto, Vicky (Prosiding University Research Colloquium, 2024)
This research was conducted to determine the effect of exhaust manifold modifications using TEC baffle one, baffle two, and baffle three, on the performance of the Honda Supra X 125. Testing was carried out using a Dynotest tool and a Honda Supra X 125 motorcycle. The results of exhaust manifold modification testing with variations in the number of TEC baffle on the performance of the Honda Supra X 125 show an increase in performance. The highest results were obtained in the modification of the exhaust manifold with TEC baffle two. The torque obtained is 9.74 Nm at an engine speed of 5000 rpm, the power produced is 7.7 HP at an engine speed of 6500 rpm, and the KBBS produced is 0.150 KG/hour. HP at a speed of 6000 rpm - 6250 rpm.